STROKE KRIPTOGENIK - Al Rasyid (Neurona Majalah Kedokteran Neuro Sains, 2009)
INTRODUCTION CRYPTOGENIC STROKE DEFINE AS ISCHEMIC STROKE WITH UNCLEAR ETIOLOGIES EVENT FULL EXAMINATION HAD BEEN DONE THIS ENTITY APPROXIMATELY CONSISTED OF 40 OF ALL ISCHEMIC STROKE INCIDENCES A FEW NEWEST TECHNOLOGIES SHOWED THAT THE ETIOLOGY OF CRYPTOGENIC STROKE CAN BE EXPLAINED THOSE ARE INCLUDE HEMATOLOGY DISORDER SUCH AS HYPERCOAGULATION STATE DUE TO DISTURBANCES IN C PROTEIN LEVEL FREE S PROTEIN LEVEL LUPUS ANTICOAGULANT OR ANTIPOSPHOLIPID SYNDROME